Development of the Past Material Composed of Learning French Using Appypie in SMA Negeri 7 Binjai - Cindy Febriyanti Simanjuntak; Junita Friska (International Journal of Educational and Life Sciences, 2024)
In this research, I examined the results of the feasibility of the method and process for developing French language teaching materials for Passé Composé using APPYPIE at SMAN 7 Binjai. The research and development method uses the ADDIE model developed by Dick and Carry (2005). The ADDIE model uses 5 development stages as follows: Analysis, Design, Development, Implementation, Evaluation. This research focuses on developing holiday material books at APPYPIE, so the research is limited to the development stage which includes: analysis, design and development. In the first stage of analysis there are two steps, namely needs analysis, then explaining each answer to each question and concluding. Then, the second main actor is the researcher who plans class equipment based on the RPS. This planning is carried out by selecting learning materials according to those listed in the RPP based on the results of interviews conducted with French language subject teachers. the second stage is the design stage. At this stage the researcher has designed material to introduce someone to other people. The material is arranged sequentially, starting from descriptions, indicators, basic skills, objectives and benefits of holiday material for others, final assignment, writing practice and a summary of the material that is easy to understand. In the third stage is development, at this stage the researcher explains the hardware in French that has been developed, explains the use of applications with this hardware and carries out the final mission. This research analysis uses a descriptive quantitative percentage approach. The feasibility results show that the educational material developed is in the "good" category with a score of 80%, and the final validation result is that the media developed is better and more relevant than with a score of 90%. which means good and can be used in French. holiday-themed language learning process. Application support can also be used to improve written production in the classroom learning process